1982
DOI: 10.1113/jphysiol.1982.sp014295
|View full text |Cite
|
Sign up to set email alerts
|

Altered developmental changes of neuromuscular junction in hypo‐ and hyperthyroid rats

Abstract: SUMMARY1. Effects of thyroid hormone on the development of neuromuscular junctions (n.m.j.s.) were investigated electrophysiologically in the diaphragms (sternal region) of normal, hypo-and hyperthyroid rats from the age of birth (day 0) to day 35.2. Hypothyroidism in new-born rats was induced either by daily administration of propylthiouracil to mothers or by subcutaneous injection of 150 1sCi l311 on day 1. Hyperthyroidism was induced by daily injection of thyroxine.3. In normal rats up to day 10, muscle fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…By day 12-l 5, y-mRNA is no longer detectable, whereas +mRNA is expressed at a maximum level. Consistent with results of earlier electrophysiological studies on the role of thyroid hormones in the maturation of the neuromuscular junction in newborn rats (Kawa and Obata, 1982), we found that thyroid hormones accelerated the switch from yto t-subunit mRNA. However, neither the dramatic postnatal rise in e-mRNA nor its sensitivity to thyroid hormones were observed in denervated newborn animals, suggesting that c-mRNA modulation is mediated by the motor nerve.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By day 12-l 5, y-mRNA is no longer detectable, whereas +mRNA is expressed at a maximum level. Consistent with results of earlier electrophysiological studies on the role of thyroid hormones in the maturation of the neuromuscular junction in newborn rats (Kawa and Obata, 1982), we found that thyroid hormones accelerated the switch from yto t-subunit mRNA. However, neither the dramatic postnatal rise in e-mRNA nor its sensitivity to thyroid hormones were observed in denervated newborn animals, suggesting that c-mRNA modulation is mediated by the motor nerve.…”
Section: Discussionsupporting
confidence: 92%
“…The similarity between the time-course of development of c-mRNA and the serum levels of thyroxine prompted us to study the role of thyroid hormones in the regulation of the switch from y-to r-subunit expression. Also in support of this hypothesis, Kawa and Obata (1982) For the purpose of assessing the role of thyroid hormone, mice were made hypothyroid by administration of PTU or hyperthyroid with thyroxine (see Materials and Methods). Figure 4 shows that in PTU-treated animals, serum thyroxine was below detectable levels.…”
Section: Role Of Thyroid Hormones In the Development Of Y-and E-mrnamentioning
confidence: 98%
“…Newborn mice were made hypothyroid by feeding pregnant females from E14 with low‐iodine Remington's diet (Mucedola, Italy) and adding 0.1 % propylthiouracil (Sigma) to their drinking water, as described by Martinou & Merlie (1991). Hypothyroid mice were markedly smaller than controls, as expected (Kawa & Obata, 1982).…”
Section: Methodssupporting
confidence: 81%
“…In hypothyroid mice, the increase in channel duration took place during the first postnatal week. This observation emphasizes the developmental significance of τ op lengthening, as in hypothyroid rats the maturation of the neuromuscular junction is comparably retarded (Kawa & Obata, 1982), and the γ subunit is still present in hypothyroid mice at P20 (Martinou & Merlie, 1991).…”
Section: Discussionmentioning
confidence: 64%
“…Instruments). When necessary, high-gain d.c. recordings were displayed with an automatic d.c.-level compensation circuit (Kawa & Obata, 1982). To measure the membrane input resistances ofneurones, small hyperpolarizing currents (0 1-0-2 nA) were injected through the recording electrode.…”
Section: Intrinsic Synapses In Mammalian Gangliamentioning
confidence: 99%